Basic Concepts in the Philosophy of Gottfried Keller - Reichert, Herbert W. (UNC Studies in the Germanic Languages and Literatures, 1949)
Originally published in 1949, this volume contains a skillful analysis of the concepts of "Natur" and "Freiheit" and their influence on Keller's ideas in the fields of ethics, aesthetics, and politics, supported by pertinent passages from Keller's work. Reichert divides Keller's works into two time periods, and includes a discussion of Schiller's influence on Keller.